An Obstacle Avoidance Scheme Maintaining Connectivity for Micro-Unmanned Aerial Vehicles - Hyo Hyun Choi; HyunSoo Choi; Myungwhan Choi; Taeshik Shon; ByoungSeob Park (International Journal of Distributed Sensor Networks)
This paper suggests an obstacle avoidance scheme that enables a group of micro-UAV (Unmanned Aerial Vehicles) to avoid colliding with an obstacle that is found in the course of the flight. This scheme considers a method for UAVs to avoid colliding with such obstacles and a plan of action for when the UAVs in the group lose connectivity during flight. The main goal is for UAVs to reach the target without colliding with any obstacles. To achieve this goal, directly after the UAVs avoid the obstacle at a raised altitude above it, they fly at a higher altitude for a while and then descend to their original height. When this approach is judged to be inefficient because the height of the obstacle is too high, the UAVs divide into two groups and move to either side of it while continuing to fly at the same altitude, thereby avoiding the obstacle. Afterwards, they gather into one group again. We verify the proposed scheme and do the performance evaluation by ns-2.